Creativity and organisational efficiency: empirical evidence from private organisations in Nigeria - Inegbedion, Henry; Inegbedion, Emmanuel; Obadiaru, Eseosa; Asaleye, Abiola; Adeyemi, Sarah; Eluyela, Damilola (Creativity Studies, 2021)
The study investigated creativity and organisational efficiency in Nigerian private organisations to ascertain the extent to which workforce creativity enhances organisational efficiency. The quantitative methodology was employed and the research design was a cross-sectional survey. Stratified sampling was employed in selecting respondents from ten multinational companies across the six geopolitical zones in Nigeria. Research data were elicited from the respondents with the help of a structured questionnaire. The question response format of items addressing the research questions in the questionnaire were of the five-point Likert scale. The study used measurement items related to the extant literature for all the measures. Structural equation modeling was employed in data analysis with organisational efficiency serving as the latent variable while creativity constructs served as the measured variables. Results show that three out of the four constructs of creativity were significant predictors of creativity Thus, the competitive environment, social capital and technological factors influence creativity and that creativity predicts organisational efficiency.